The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1109/26.602584
|View full text |Cite
|
Sign up to set email alerts
|

Symbol-by-symbol MAP demodulation of CPM and PSK signals on Rayleigh flat-fading channels

Abstract: Demodulation using the symbol-by-symbol maximum a posteriori probability (MAP) algorithm is presented. The algorithm is derived for the case of continuous phase modulation (CPM) signals transmitted over Rayleigh flat-fading channels, and a corresponding receiver structure is specified. It is shown that the MAP algorithm requires computing, for each trellis branch, the sum of the products of the weights of all paths through the trellis which pass through that branch, and that this generic computational problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 20 publications
0
74
0
Order By: Relevance
“…Alternatively, a number of sub-optimum detectors have been proposed, but the required computational burden is still high [3], [4]. In terms of blind methods, [5] showed that the constant modulus criterion is not capable of equalizing a CPM signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a number of sub-optimum detectors have been proposed, but the required computational burden is still high [3], [4]. In terms of blind methods, [5] showed that the constant modulus criterion is not capable of equalizing a CPM signal.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, considering the full-response modulation and using (4), the signals at the output of the receiver shown in figure 1 will be:…”
Section: B the Lrc Modulationmentioning
confidence: 99%
“…In related work, Gertsman and Lodge [GL97] showed that the forward-backward algorithm, with per-branch linear prediction, can be used for near-MAP symbol detection under AR time-selective channels and CM alphabets. Independently, these ideas were generalized this approach to doubly selective channels and general signal alphabets by Hart and Pasupathy [HP00] and Davis, Collings, and Hoeher [DCH01].…”
Section: Near-optimal Trellis-psp Equalization For Single-carrier Schmentioning
confidence: 99%
“…The FB algorithm in (14) operates on a trellis whose number of states is the number Ξ of states of the modulator-channel FSM times the number L of states of the channel parameter Markov chain. This can be interpreted as a "super-trellis" comprising L trellises, each with Ξ states.…”
Section: Appendixmentioning
confidence: 99%
“…In the case of phase-uncertain communications, parameter estimation may be embedded in the detection process, explicitly [5] or implicitly [6]- [9]. In [10]- [14], linear predictive receivers for fading channels are proposed, considering the Clarke model for fading channels [15], [16]: these receivers exploit the correlation characteristics of the fading process to predict its evolution. Another general approach consists of describing the evolution of the fading process through a suitable Markov chain [17]- [19], and then taking this model into account in the receiver design [20]- [24].…”
mentioning
confidence: 99%